Integration Of Digital Learning Media Based On Socio-Scientific Issues On Students' Literacy Abilities At School - Fakhrah Fakhrah; Riska Imanda; Sri Ayuni Rambe; Nurul Faudina Aini (LPPM Universitas Malikussaleh, 2024)
Abstract. This research is a quantitative study that aims to determine the effect of implementing digital learning media based on socio-scientific issues on students' literacy abilities. The sampling technique was carried out by purposive sampling where each class consisted of 30 students. The data collection instrument used was chemical literacy test questions. Before an instrument is tested on a research sample, it must be tested. The research results showed that the literacy skills of experimental class students who had been given digital learning media based on socio-scientific issues were better than students in the control class. The average percentage score for the experimental class was 97% with a very good predicate, while for the control class, the average percentage score was 63.33% with a fair predicate. Based on the results of normality and homogeneity tests, the research data is normally distributed and has the same homogeneous variance data. There are t-test results from student test results with a sig value. (2-tailed) = 0.000. This means that in this case the sig value. (2-tailed) 0.000 < 0.05, meaning that H0 is rejected and H1 is accepted, so in this study, it can be concluded that there is an influence of the application of digital learning media based on socio-scientific issues on students' chemical literacy abilitiesKeywords: keyword 1; keyword 2; keyword 3 (List three to five pertinent keywords specific to the article yet reasonably common within the subject discipline.)